2023
DOI: 10.1021/acsami.2c18389
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Ti(IV) in Ce-UiO-66-NH2 Metal–Organic Frameworks Increases H2 and O2 Evolution under Visible Light

Abstract: Metal–organic frameworks (MOFs) as photocatalysts have received increasing attention. In this work, a dual metal-substituted UiO-66-NH2 (Ti/Ce-MOF) containing different Ti/Ce mole ratios (x = 0–2.46) has been prepared via post-synthetic exchange between Ce-UiO-66 and TiCl4, followed by amination. The solid had a high surface area (828–937 m2/g) and a large pore volume (0.451–0.507 m3/g). Under visible light, Ti/Ce-MOF showed x-dependent activity for H2O reduction and oxidation on a film electrode, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The as prepared and activated UiO-66-NH 2 (Ce) MOF was initially characterized by powder XRD (pXRD) to ensure purity and crystal structure. The pXRD pattern of the solid product (Figure a) revealed set of reflections which can be indexed to pure UiO-66-NH 2 (Ce) MOF as reported in literature. , Moreover, it is well-known fact that amine (−NH 2 ) group is an excellent functionality for anchoring different functional groups, leading to tailor-made MOF materials for targeted applications . Thus, it was perceived that modification of the tethered amine group by diphenylphosphinyl (Ph 2 PO−) group fixation to afford −NHPOPh 2 (phosphinic amide) functionality could enhance the uranium uptake capacity of the MOF, which is the primary aim of the present work.…”
Section: Resultsmentioning
confidence: 65%
“…The as prepared and activated UiO-66-NH 2 (Ce) MOF was initially characterized by powder XRD (pXRD) to ensure purity and crystal structure. The pXRD pattern of the solid product (Figure a) revealed set of reflections which can be indexed to pure UiO-66-NH 2 (Ce) MOF as reported in literature. , Moreover, it is well-known fact that amine (−NH 2 ) group is an excellent functionality for anchoring different functional groups, leading to tailor-made MOF materials for targeted applications . Thus, it was perceived that modification of the tethered amine group by diphenylphosphinyl (Ph 2 PO−) group fixation to afford −NHPOPh 2 (phosphinic amide) functionality could enhance the uranium uptake capacity of the MOF, which is the primary aim of the present work.…”
Section: Resultsmentioning
confidence: 65%
“…Recently, Ho and Paesani used molecular dynamics to explain the competitive behavior of H 2 O and CO 2 on CALF-20. 56 They showed that in the presence of CO 2 , water molecules form a more connected hydrogen-bonded network that decreases water entropy leading to a retardation in its capacity. Such a unique behavior where the presence of CO 2 retards H 2 O adsorption, to the best of our knowledge, has not been noticed before.…”
Section: Competitive Co 2 + H 2 O Dynamic Column Breakthrough Resultsmentioning
confidence: 99%
“…[ 1‐14 ] TOCs are adorned with various functional ligands, including carboxylates, phosphonates, sulfates, azoles, calixarenes, hydroxyls, and more. [ 15‐27 ] These ligands play crucial roles in modulating the cluster structures and physicochemical characteristics, while also offering abundant applications in photocatalysis, semi conductivity, environmental remediation (such as dye degradation), and wastewater treatment. [ 28‐38 ] Moreover, recent advances in the decagram‐scale synthesis of TOCs for various applications show their commercial potential as future sustainable catalysts to be utilized at the industrial scale.…”
Section: Background and Originality Contentmentioning
confidence: 99%